Aksiologi Melayu Islam dan Manifestasi Komunikasi Organisasi dalam Film Mat Kilau: Kebangkitan Pahlawan - Siregar, Dzulhajj Aeyn Abe; Kurniawati, Dewi (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The exposing of Islam around Nusantara has been occure since the first generation that resulting unseperated integration within Malay. Including Pahang, sovereign in sultanate whose supremely loyal to Ottoman Caliphate. But since The Pangkor Treaty of 1874, The British starts overpower several administration position to posses goods of Pahang’s earth. Power and physical penetration done by The British colonialism contradicts to the natural recognition and human rights of syari’ah also motivates the amir, ulama, and mujahid to revolt (Saayah Ismail et al., 2019). This epic then adapted in the film Mat Kilau: Kebangkitan Pahlawan (2022)” that manisfestating axiology of Islamic Malay. Along with that also recognized several form of Organizational Communication among the movement. This film is interpretated by Articulation of Film’s Theory by Worth, S. Validated by Historical Situatedness some of literature about Pahang wrote by Saayah Ismail dkk (2019), Mugiyono (2016), Sunandar (2019), and Shukri & Abidin (2023) verify the result. The literary propositions of the Qur'an and al-Ḥadīṡ are found axiologically in both dialogue and play. Advice for film semiotics researchers is to know that screenplays or storyboards which are adaptations of literature, both fiction and factual, are references that should be accessible rather than merely interpreting symbols.